COMMENT WAR IN TURKEY ELECTIONS 2023: A POLITICAL NETNOGRAPHY ANALYSIS - Mahmud Yunus Mustofa; Fentika Zahra Qoirunnisa; Firmanda Taufiq (CMES (Center of Middle Eastern Studies), 2024)
Social media platforms have recently emerged essential to electoral politics and democratic processes worldwide. The uninhibited flow of ideas and opinions between fans can frequently be seen in the comment areas of social media platforms. This article analyzes the Instagram Middle East Eye (MEE) comment war, emphasizing the 2023 Turkish elections. We use political netnography to evaluate one of David Hearst's thoughts on Instagram MEE. We categorize comments based on Recep Tayyip Erdoğan and Kemal Kılıçdaroğlu. We discovered that public opinion is divided into two camps: secularists and Islamists. Groups advocating secularism use arguments about the Turkish economy's collapse and the freedom of the media in Turkey during Erdogan's rule. On the other side, Islamists argue that only Erdogan has the guts to speak out boldly in support of freedom for the Islamic community that is currently at odds. According to them, Turkey protects Muslims all around the world. They also claimed that the West and Europe interfered in Turkey's elections in order to weaken Islam. They stated that the intervention was taking place. The research is critical because the election in Turkey in 2023 is one of the most important elections that will change the map of Islamic power against the West.